2020
DOI: 10.1002/jcp.29425
|View full text |Cite
|
Sign up to set email alerts
|

Red orange and lemon extract prevents the renal toxicity induced by ochratoxin A in rats

Abstract: In this work, we investigated the effects of red orange and lemon extract (RLE) on ochratoxin A (OTA)‐induced nephrotoxicity. In particular, we analyzed the change in renal function and oxidative stress in Sprague–Dawley rats treated with OTA (0.5 mg/kg body weight, b.w.) and with RLE (90 mg/kg b.w.) by oral administration. After OTA treatment, we found alterations of biochemical and oxidative stress parameters in the kidney, related to a severe decrease of glomerular filtration rate. The RLE treatment normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
6
28
0
Order By: Relevance
“…Therefore, the main antioxidant enzymes, such as CAT, SOD and GPx, play a crucial role in protection against oxidative stress [39]. The results obtained in this study, in accordance with our previous works [7,21,27], confirmed that the renal toxic effects of OTA, both on a functional and histopathological level, is mediated by oxidative stress. Actually, in this study we found an increase of MDA in the kidneys of rats treated with OTA, which is an index of membrane lipid damage, and a decrease mainly in the activity of GPx, in line with the study conducted by Bertelli, et al [40,41].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, the main antioxidant enzymes, such as CAT, SOD and GPx, play a crucial role in protection against oxidative stress [39]. The results obtained in this study, in accordance with our previous works [7,21,27], confirmed that the renal toxic effects of OTA, both on a functional and histopathological level, is mediated by oxidative stress. Actually, in this study we found an increase of MDA in the kidneys of rats treated with OTA, which is an index of membrane lipid damage, and a decrease mainly in the activity of GPx, in line with the study conducted by Bertelli, et al [40,41].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the administration of antioxidants that counteract oxidative stress may protect kidneys from damage. Nephrotoxicity studies have confirmed the authentic roles of bioactive compounds to reduce chronic renal failure [27,[34][35][36]. The present study investigated CURC effects on OTA-induced toxicity using an in vivo animal model.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Some advances in cancer therapies have been recently reached thanks to the introduction of alternative approaches, including the use of several phytochemicals which are able to significantly reduce tumor progression and to improve healing and survival [24][25][26].…”
Section: Phytochemicals As Anti-cancer Molecules: the Example Of Curcmentioning
confidence: 99%